Ibnu Rusyd's Thinking And Deradicalization Education (Study of Epistemology of Interpretation of Islamic Texts) - Afwah Mumtazah (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Radicalism among Muslims has long emerged as a result of the interpretation of religious texts. On a practical level, radicalism can take the form of radicalism and intolerance movements in Indonesia, especially when approaching the election of a democratic party such as the election of the President or Governor. The phenomenon of radicalism and intolerance actually existed at the time of Ibn Rushd. This study will discuss the idea of Ibn Rushd's deradicalization. This research is a qualitative research based on library research. The method used is content analysis. The primary data is extracted from the works of Ibn Rushd. The secondary is taken from several books, journals and internet related to the study. The approach used is sociological by borrowing conflict and functional theory. The results of this study explain that according to Ibn Rushd the takwi path can be chosen as an alternative, so that problems can be solved without making offense. In practical terms, Ibn Rushd's int